Karakteristik Statistik Kanal Radio HF Domain Waktu Pada Band Maritim - Sutoyo Sutoyo (UIN Sultan Syarif Kasim Riau, 2012)
Technological advances in HF channel can be used for communication on maritime. An increasing number of users resulted in the occupation of the channel have different data characteristics. Expression of a signal can be expressed in the time domain or in frequency domain. In this research modeling the statistical characteristics of data the use of HF radio channel in time domain to sound signals through the measuring process. Measurements are grouped into the measurement time in the morning, afternoon, evening and night are categorized into small medium and dense traffic. The results of the measurement data and modeled through a statistical approach to data distribution to get the average service time at each measurement time. From the time available to do the estimated length of service data packet may be sent the system to be used. The results of data processing and modeling that the data obtained using the HF radio channel in time domain exponentially distributed the availability of most of the time of service there at night by 27.9 seconds and the estimated length of the packet obtained by 104.6 KbyteKeywords: HF, time domain,data modeling, service time